Opportunities to Elevate Levels of Curcumin in Curcuma xanthorrhiza Plants - Pertamawati, Pertamawati (Jurnal Jamu Indonesia, 2018)
Production of curcuminoids from Curcuma xanthorrhiza using conventional cultivation technique requires a very long time from planting to harvesting process. The use of biotechnology known as the callus culture is expected to help this problem. An experiment was conducted with the explant of curcuma leaves which are cultured in basic media of Murashige & Skoog (MS) with addition of growing substances Phenilalanine (2-amino-3-fenil-propanoat acid/C9H11NO2) with a concentration of 2, 4 and 8 mg/L and Sodium Acetate (CH3COONa) with concentration of 0.2 and 4 mg/L. Experiments done with random design with 3 times replication. The results showed that addition of Phenilalanine at a concentration of 4 mg/L produced curcuminoids namely curcumin 0.8861% and desmethoxycurcumin 0.3307%, while the addition of sodium acetate 2 mg/L was able to induce the formation of curcuminoids namely curcumin 0.7514% and desmethoxycurcumin 0.3898%. It is suggested that further research with a callus induction technology in tissue culture need to be conducted for producing curcumin in an industrial scale.